PENGARUH PEMBERIAN REWARD, PUNISHMENT, DAN KERJASAMA TIM TERHADAP KINERJA PEGAWAI PT. KERETA API INDONESIA (PERSERO) DIVRE IV TANJUNG KARANG (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
This study discusses the influence of giving rewards, punishments and teamwork on the employees’ performance of PT. KeretaApi Indonesia (Persero) DIVRE IV TanjungKarangBaturaja Station. The data collection technique used in this writing is through the distribution of questionnaires. The total population in this study were 34 people. The analytical method used is a quantitative method using multiple linear regression analysis tools. Based on the results of the analysis that has been carried out, it is concluded that either partially or simultaneously giving rewards, punishments and teamwork to the performance of PT. KeretaApi Indonesia (Persero) DIVRE IV TanjungKarangBaturaja Station. The coefficient of determination (Adjusted R square) is 0.564. This means that the contribution of the variable effect of reward, punishment and teamwork on employees’ performance is 56.4% while the remaining 43.6% is influenced by other variables besides the variables in this study, namely work motivation, responsibility, work discipline and incentives ( Sedarmayanti, 2017:228).